Fluid mechanics - Mohanty, A.K (Prentice Hall, 1994)
The book gives a thorough analysis of topics such as fluid statics, fluid kinematics, analysis of finite control volumes, and the mechanical energy equation. It provides a comprehensive description of one- dimensional viscous flow, dimensional analysis, two-dimensional flow of ideal fluids, and normal and oblique shocks.